Evaluation of Bacillus amyloliquefaciens UG7 in improving cassava leaf meal as a raw material for fish feed. Issue 1 (October 2021) - Mulyasari,; Melati, Irma; Yosmaniar,; Subaryono,
Abstract: Cellulolytic bacteria can be used to improve the quality of cassava leaf meal by reducing fiber and simplifying other nutrients such as protein and carbohydrate. The use of this cellulolytic bacteria will have an impact on increasing the digestibility of the material so that its utilization as feed raw material can be increased. This study aimed to evaluate the ability of cellulolytic bacteria Bacillus amyloliquefaciens UG7 in improving the quality of cassava leaf meal as raw material for fish feed. The study was conducted using a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment was cassava leaf meal fermented using B. amyloliquefaciens UG7 that isolated from Turbinaria with four doses of inoculum, namely 0%, 5%, 10%, 15%. Cassava leaf meal incubation was carried out at 28°C (room temperature) for 3 days. The parameters observed were reducing sugar, water-soluble protein, crude fiber, digestibility. The results showed that the use of these bacteria can increase reducing sugars, water-soluble proteins and reduce the crude fiber content of cassava leaf meal. A dose of 15% bacteria yields the highest value for water-soluble protein and reducing sugar and produces the lowest value for crude fiber content. However, the fermentation process of cassava leaf meal with B. amyloliquefaciens did not significantly influence the total digestibility of material.